What makes you move? A minimalist study of object displacement in English Double Object Construction - Bartczak-Meszyńska, Aleksandra (LingBaW. Linguistics Beyond and Within, 2015)
The aim of this paper is to analyse the displacement phenomena the direct and indirect objects in the English Double Object Construction (DOC) can undergo. The focus is on the movement out of the DOC to the sentence initial position. The analysis concerns not only globally acceptable Goal-Theme object sequence but also the Theme-Goal DOC, which grammaticality is restricted only to a few British English dialects. The processes affecting the objects in the Prepositional Construction are also mentioned. The initial part of the paper is devoted to the underlying syntactic representations of the DOC in English. Following, e.g. Citko (2011), Cuervo (2003), Pylkkännen (2002, 2008), a representation with the Low Applicative Phrase has been adopted. The exact case valuation mechanism for relevant objects (as proposed by Bondaruk and Bartczak-Meszyńska (2014)) has been established. The remaining part of this paper contains a detailed discussion of the derivation of particular object initial sentences with the DOC in the active and in the passive and the interplay between passivisation and topicalisation, as the triggers of the object fronting.